2012
DOI: 10.1007/s10544-012-9688-x
|View full text |Cite
|
Sign up to set email alerts
|

Telemetry capsule for measuring contractile motion in the small intestine

Abstract: The aim of this study was to develop a capsule which can measure contractions in the small intestine. Currently available methods cause discomfort to the patient while taking measurements; with the development of a telemetry capsule that can measure contractions, patients can avoid pain and continue with ordinary activities while the information is automatically collected from the external receiver. In order to develop the contraction force measuring capsule, various types of silicone transducers were designed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…The frequency of CTE depends on the frequency of contraction inside the GI tract and there is no unique value for it in the literature. Woo et al [13] measured the small intestine contractile motion using a telemetry capsule, and the periodic pressure of the small intestine is shown as Fig. 4.…”
Section: Simulation Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The frequency of CTE depends on the frequency of contraction inside the GI tract and there is no unique value for it in the literature. Woo et al [13] measured the small intestine contractile motion using a telemetry capsule, and the periodic pressure of the small intestine is shown as Fig. 4.…”
Section: Simulation Resultsmentioning
confidence: 99%
“…Periodic pressure of the small intestine[13] The output power versus resistance for a. constant velocity motion and b. variable velocity motion When the resistance reaches 1GΩ and 5GΩ, the output power reaches its maximum values of 0.4 and 0.54 mW for the constant velocity and variable velocity motion, respectively.…”
mentioning
confidence: 99%
“…They also reported that peristalsis velocity of the small intestine is 2.2 cm/min during fasting period and 2.3 cm/min in postprandial period, and the gastric contraction frequency is 2.85 ± 0.29/min. Arman et al [30] reported the hoop pressure measured by a telemetry capsule. However, the in vitro test can only measure the hoop stress caused by small intestine extension (when the diameter of capsule is larger than the diameter of the small intestine).…”
Section: B Transit Time and Pressurementioning
confidence: 99%